Determinação da validade e reprodutibilidade de um instrumento de avaliação odontológica em idosos aplicado por agentes comunitários de saúde e do treinamento para seu uso - Marco Tulio de Freitas Ribeiro (2012)
The Community Health Agent (CHA), to be a relationship between the community and health services can contribute in organizing strategies of oral health care for the elderly, through pre-diagnostic tests and referral of individuals with oral abnormalities. The aim of this study was to determine the validity and reproducibility of a pre-diagnostic tool "Revised Oral Assessment Guide" (Roag), and discuss the adequacy of this instrument when applied by ACS. The evaluation of Roag was through a cross-sectional study, in a first phase. In the second phase, we assessed the training to use Roag and the feasibility of their use by ACS through a qualitative approach. The test instrument was driven by its application for ten ACSs in a large municipality. The Roag assesses the health condition of 8 categories: voice, lips, buccal mucosa, tongue, gingiva, hygiene of teeth and dentures and / or caries, swallowing saliva, from a scale that gives values 1-3 to each these. The calculation of the sample, n = 116, Senior, was done by formula recommended by the Pan American Health Organization (PAHO), for this type of study. To assess the validity and reproducibility of Roag, four steps were conducted. At first the suitability of the instrument, which was named the Oral Assessment Guide Revised (GABR) was taken; the second a program for prior training of ACS was developed; the third was done the training and the pilot study; the last step the instrument was administered. The second phase of study adopted a qualitative approach through focus group technique. The ACS who participated in the first phase of the study were invited to participate in the focus group, and seven of them were willing to participate. The focus group took place on time and place determined by the coordination of oral health in the municipality of the study. The statements of ACS were recorded and an observer noted in daily field observations on the attitude and posture of ACS. Transcription of the speeches was taken keeping the original spelling and syntax, and the results were subjected to content analysis. The average time for completing the GBR was 11 minutes. Regarding the reproducibility found the following: intra-rater categories in voice and swallowing were perfect (kappa = 1.00) buccal mucosa (Kappa = 0.84), language (Kappa = 0.75) and gingiva (Kappa good = 0.87) or very good agreement, and reasonable for the category saliva (Kappa = 0.48). Regarding the validation is found to instrument sensitivity to changes ranged between 0.80 to 0.17 for voice evaluation of saliva. The speech analysis of ACS who participated in the focus group revealed that they considered the positive training method, although considering the short time. We conclude that guide Revised Oral Assessment shows good productivity and validity to be used as an instrument pre-diagnosis when used by trained Community Health Agents, and that the training method used in this study was good, in the opinion of these professionals. ACS is required for the use of GABR routinely be accompanied by assistance to current demand.